Monitoring bacterial processes by Fourier transform infrared spectroscopy: Helicobacter pylori drug inactivation and plasmid bioproduction in recombinant Escherichia coli cultures - Scholz, Teresa (2020)
Fourier transform infrared (FTIR) spectroscopy is evaluated as a tool to monitor two bacterial processes: strain discrimination and drug inactivation studies with the gastric pathogen Helicobacter pylori and the plasmid production process based on high-density cultures of recombinant Escherichia coli. Results show, that after evaluation of different incubation conditions of H.pylori with the drug model, the application of principal component analysis to the FTIR spectra assembles the samples into clusters which can be related with the minimal inhibitory concentration. Morever, the same methodology applied to FTIR spectra from 12 different strains can be used to distinguish them. For the E.coli cultures it is possible to estimate the concentration of relevant bioprocess monitoring variables, such as plasmid, biomass, and carbon sources (glucose, glycerol, acetate) by using partial least squares (PLS) models based on FTIR spectra.